Numerical analysis of turbulent flow around two-dimensional bodies using non-orthogonal body-fitted mesh - Tarafder, Md. Shahjada; Mursaline, M. Al (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the numerical simulation of a turbulent flow around two-dimensional bodies by the finite volume method with non-orthogonal body-fitted grid. The governing equations are expressed in Cartesian velocity components and solution is carried out using the SIMPLE algorithm for collocated arrangement of scalar and vector variables.
Keywords: turbulent flow; finite volume method; pressure distribution